Trading and Attentional Focus – Why we may overestimate the Impact of the Endowment Effect - Stephan Tontrup (ZBW - Leibniz Information Centre for Economics, 2019)
Most Endowment Effect studies incentivize individuals to reveal their true valuation when sell ing their entitlement. This experimental design can mislead the legal debate because it focuses sellers' attention on their endowment and thereby elevates the size of their bias. In our study, we place subjects in a market with incentives for strategic trading behavior. As in real markets, participants can increase their profits by demanding sales prices beyond their true valuations. We assume that the strategic market incentives shift the sellers' attention from their entitlements to the gains from trade and to estimating the WTP of potential buyers. Trading in the strategic market environment reduced the Endowment Effect drastically, to a highly insignificant one fifth of its original size (cohen's d -0.14). We support the debiasing effect with direct evidence, showing that both the impact of loss aversion and regret on the trade vanish under these conditions. Finally, we show that employing more than one market institution reinforces the debi asing effect. To test this assumption, we provide the subjects with agents who carry out the trades following each subject's instructions. With the two institutions, strategic markets and agency, debiasing the sellers, the gap between WTA and WTP prices disappeared completely. Our findings should apply to the large majority of market transactions. Most businesses and private sales trade for profit. We conclude that the Endowment Effect may have far less impact on private ordering than typically suggested in the legal literature.
Keywords: 330; Endowment; Trading (strategic price setting); Attentional Focus; Markets